KINERJA KARYAWAN PADA KANTOR PERSEROAN TERBATAS PERKEBUNAN NUSANTARA XIII (PERSERO) KEBUN SUNGAI DEKAN DI KECAMATAN MELIAU KABUPATEN SANGGAU - Ricky Edward BB E.01106101 (PublikA, Jurnal Ilmu Administrasi Negara, 2013)
An operating company in need of employees with high performance. Given the employees are important assets a company or an organization then a lot of things that need to be considered related increase in performance. This study aims to determine the quantity of work, quality of work and timeliness of work of employees in the Administrative Core PT. PTPN XIII (Persero) Kebun Sungai Dekan. The research subjects are 13 people consisting of Manager, Chief Administrative Core, and Core Administration Employees using purposive sampling technique. In this study the authors use a type of descriptive study with a qualitative approach. Data collection techniques are observation, interview and documentation. The results showed that there are problems that hinder employee performance of the Core Administration as the amount of work to be done to reach the target arrives apparently not been determined, the work was not done properly so it gets a lot of improvement and correction of the leaders, and employees have not been fully able to take advantage of the time work optimally. Based on these studies it can be concluded that the employee indicates that the quantity is low which includes the achievement of targets, work overtime and compliance with the number of employees. Quality of employment is still low which includes neatness, thoroughness, skill and initiative. Employee timekeeping largely on time on the job and not take advantage of the time as possible in the work. Suggestions given are preferably added headcount, employees should increase accuracy in carrying out their work in order to avoid mistakes, and regulations on working time came and went and came out during working hours should be tightened. Keywords: Employee Performance, Quantity Work, Work Quality, Timeliness